BUDAYA TERLAMBAT GURU DAN TENAGA KEPENDIDIKAN SEBAGAI FAKTOR PENGHAMBAT PEMBERIAN KOMPENSASI JABATAN DI SEKOLAH - Dyas Bintang Perdana; S. Sultoni (Jurnal Administrasi Pendidikan, 2021)
This research aims to determine the problems that occur in the process of giving compensation that occurred at SMP 6 Muhammadiyah Malang. The research method used is qualitative research. The data source in this study was the principal of SMP 6 Muhammadiyah Malang who gave direct information from in-depth interviews conducted and also related documentation studies. The analysis is carried out by the stages of finding out first the problems that occur, analyzing the problem and then providing alternative solutions for solving the problem. The research carried out obtained the main problem, namely the culture of being late for teachers and education personnel which caused problems in providing compensation in the form of positions in school structural organizations.